A Study of Polymerase Chain Reaction in Cerebrospinal Fluid for Diagnosis of Tuberculous Meningitis - Gupta, Sheena; Gupta, Alpa; Wasim, Sanober; Kotwal, Aarti; Bhat, Nowneet Kumar (National Journal of Community Medicine, 2016)
Introduction: Tuberculous Meningitis (TBM) is the commonest type of CNS tuberculosis encountered in children of India. This study was undertaken to evaluate the role of TB Polymerase Chain Reaction (PCR) in CSF for rapid diagnosis of TBM. Methods: All children having CNS illness and undergoing CSF examination were included in the study and were grouped into two. Group I (Study Group) were subjects with the clinical evidence along with one or more of the laboratory or radiological evidence for tuberculous meningitis. Group II (Control Group) comprised of subjects who were diagnosed to have CNS illness other than tuberculous meningitis undergoing CSF examination. CSF samples from all the subjects were subjected to AFB staining, culture and PCR for Mycobacterium tuberculosis. Results: A total of thirty three subjects were enrolled in the study of which 18 were in Group I and 15 were in Group II. The sensitivity and specificity of TB PCR for diagnosis of TBM was 77.78% & 100%, respectively and positive predictive value was 100% and the negative predictive value was 78.95%. Conclusion: Analysis of TB PCR in CSF is a sensitive tool with high specificity for making rapid and accurate diagnosis of TBM.